International lower secondary science workbook 1 - Leng, Ho Peck (Marshall Cavendish Education, 1999)
The "International Lower Secondary Science Workbook 2" is a supplementary resource designed to accompany the main textbook for lower secondary students (ages 12-14). It provides a variety of exercises, activities, and practice questions that reinforce the key scientific concepts covered in the textbook. The workbook focuses on hands-on learning, problem-solving, and application of knowledge in biology, chemistry, and physics. It includes practical tasks, diagrams, and assessments that help students test their understanding, develop critical thinking skills, and prepare for exams.